Centralization of health policy decisions, conversion to austerity, and public defiance in contemporary France. Issue 4 (1st March 2021) - Simonet, Daniel
Abstract : France has experienced significant social policy changes in the last 20 years, which are perceived to be paradigm shifts. The paper informs the reader about the implementation of New Public Management (NPM) principles in the French health care system and its limitations. NPM developments change the healthcare environment, but its outcomes were below expectations. Reforms led to a recentralization of health policy decisions, eased the implementation of austerity measures, but adversely affected key stakeholders such as the medical profession and the public. Reforms pitted the Medical Profession against the Techno Structure. Public participation and civic engagement are receding.